Hepatic miR‐126 is a potential plasma biomarker for detection of hepatitis B virus infected hepatocellular carcinoma. Issue 11 (8th February 2016) - Ghosh, Amit; Ghosh, Alip; Datta, Somenath; Dasgupta, Debanjali; Das, Soumyajit; Ray, Sukanta; Gupta, Subash; Datta, Simanti; Chowdhury, Abhijit; Chatterjee, Raghunath; Mohapatra, Saroj Kant; Banerjee, Soma
Abstract : Controversies about the origin of circulating miRNAs have encouraged us to identify organ specific circulating miRNAs as disease biomarkers. To identify liver‐specific miRNAs for hepatocellular carcinoma (HCC), global expression profiling of miRNAs in liver tissue of HBV‐HCC and HBV‐control with no or mild fibrosis was evaluated. A total of 40 differentially expressed miRNAs were identified in HCC. Among ten highly altered miRNAs, six miRNAs were successfully validated in tissues, whereas only two miRNAs, miR‐126 and miR‐142‐3p showed increased expression in plasma of HBV‐HCC compared to HBV‐non‐HCC patients. Subsequently, ROC curve analysis revealed that neither miR‐126 nor miR‐142‐3p performed better than AFP in discriminating HCC from non‐HCC while combination of each with AFP showed significantly higher efficiency rather than AFP alone (AUC: 0.922, 0.908 vs . 0.88; sensitivity: 0.84, 0.86 vs . 0.82 and specificity: 0.92, 0.94 vs . 0.86 respectively). Interestingly, triple combination of markers (miR‐126 + miR‐142‐3p + AFP) showed no additive effect on efficiency (AUC: 0.925) over the dual combination. Again, the expression of only miR‐126 was noticed significantly higher in HBV‐HCC patients with low‐AFP [<250 ng/ml] compared to either non‐HCC or liver cirrhosis (AUC: 0.77, 0.64, respectively). Furthermore, no alteration in expression of mir‐126 in HCV‐HCC or non‐viral‐HCC revealed that miR‐126 + AFP might be specific to HBV‐HCC. To understand the physiological role of these two miRNAs in hepato‐carcinogenesis, target genes related to cancer pathways (APAF1, APC2, CDKN2A, IRS1, CRKL, LIFR, EGR2) were verified. Thus, combination of circulating miR‐126 + AFP is a promising noninvasive diagnostic biomarker for HBV‐HCC and may be useful in the management of HCC patients. Abstract : What's new? The incidence of hepatocellular carcinoma (HCC) in India is suspected to be on the rise. However, standard HCC detection tools, namely measurement of α‐fetoprotein (AFP) levels, may not be effective in Indian populations. According to this study, AFP levels are below detection limits in more than 35% of Indian HCC patients. The detection of early‐stage liver malignancy in patients with low AFP levels may be possible, however, with the use of a novel biomarker, microRNA‐126 (miR‐126). The authors describe the detection of miR‐126 in circulating plasma and its potential to detect HCC in combination with AFP.